2003
DOI: 10.1002/cncr.11481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ThinPrep and conventional smears in detecting carcinoma in bile duct brushings

Abstract: BACKGROUND.Bile duct brushing cytology is a common procedure for the exclusion of adenocarcinoma in the bile duct. The authors evaluated the use of ThinPrep (TP) to determine whether the information obtained is equivalent to that found with conventional smear cytology (CS). METHODS.Thirty-eight prospectively collected endoscope retrograde cholangiopancreatography-guided bile duct brushing samples were split in the following manner. First, two to four CS were prepared and immediately spray-fixed or wet-fixed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…TLC can be easily applied to the material collected (including brushings) from the biliary and pancreatic ducts and the diagnostic results are quite promising. The series of Siddiqui et al 11 and Duggan et al 12 show that the ThinPrep applied to brushings during ERCP decreases the rate of inadequate diagnoses (including those related to air drying or mechanical artefacts) even when the 'split-sample' method is used. On the other hand, the liquid fixation may induce a relative cellular shrinkage which is responsible for some false-positive diagnoses.…”
Section: Urinary Cytologymentioning
confidence: 99%
“…TLC can be easily applied to the material collected (including brushings) from the biliary and pancreatic ducts and the diagnostic results are quite promising. The series of Siddiqui et al 11 and Duggan et al 12 show that the ThinPrep applied to brushings during ERCP decreases the rate of inadequate diagnoses (including those related to air drying or mechanical artefacts) even when the 'split-sample' method is used. On the other hand, the liquid fixation may induce a relative cellular shrinkage which is responsible for some false-positive diagnoses.…”
Section: Urinary Cytologymentioning
confidence: 99%
“…75 The overall diagnostic sensitivity and specificity were 59.8% and 98.1% in a series of 406 patients with pancreato-biliary strictures, and these improved from 44.3% and 96.4%, respectively, in the initial one third to 70.7% and 97.1%, respectively, in the final third of cases. 75 The overall diagnostic sensitivity and specificity were 59.8% and 98.1% in a series of 406 patients with pancreato-biliary strictures, and these improved from 44.3% and 96.4%, respectively, in the initial one third to 70.7% and 97.1%, respectively, in the final third of cases.…”
Section: What Is the Incidence Of A Benign Pathology In Patients Presmentioning
confidence: 90%
“…18 A recent review summarized various studies that compared liquid-based with cytocentrifugation or other conventional slide preparations, including associated differences in morphology resulting from the different methods of preparation. 19 Numerous studies have reported diagnostic sensitivities using ThinPrep Non-Gyn filters for GI specimens, 5,10,[12][13]20 with ThinPrep showing improved sensitivity for malignancy over other methods such as cytocentrifugation or conventional smear preparations. 5,10,12 Three large studies reported similar sensitivities of 51-53% for ThinPrep slides, whereas a lower sensitivity of 15% for bile duct cytology using ThinPrep slides has been reported as part of dual cytology/FISH testing for GI specimens.…”
Section: Split Sample Validation Study: Preparation Qualitymentioning
confidence: 99%
“…Slides prepared using LBC methodologies may offer improved cel-lularity and cellular preservation. [7][8][9] Several studies have addressed the morphology and performance of ThinPrep Non-Gyn filter slide preparations in GI cytology, [10][11][12][13][14][15] but there have been no prior reports on the use of the Thin-Prep UroCyte filter for nonurine specimens. A study evaluating UroCyte filter slide preparations for UroVysion FISH using urine specimens has been reported.…”
mentioning
confidence: 99%